ELECTRONIC SURVEILLANCE AND HISTORICAL DEVELOPMENT OF SURVEILLANCE CONCEPT - ÖZGER, Özgün (Cyberpolitik Journal, 2016)
Surveillance is as old as human history. Since ancient times, the practice of surveillance in terms of governments and sovereignty has become a feature affecting every aspect of human life. In today’s world-termed as information era, surveillance practices have gained importance which has never had before. Surveillance, which is based on the means of purely high technology, has no longer been satisfied with just providing social control. With the personal data processing capacities of digital technology, individuals are beginning to become part of the digital code. In this study, the concept of surveillance and the historical background of surveillance have been examined. Electronic surveillance, which is a surveillance system of this age, has also been taken into consideration, including surveillance instruments.